The Perception of Mandarin Lexical Tones by Native Speakers of Burmese. (December 2019) - Tsukada, Kimiko; Kondo, Mariko
This study examines the perception of Mandarin lexical tones by native speakers of Burmese who use lexical tones in their first language (L1) but are naïve to Mandarin. Unlike Mandarin tones, which are primarily cued by pitch, Burmese tones are cued by phonation type as well as pitch. The question of interest is whether Burmese listeners can utilize their L1 experience in processing unfamiliar Mandarin tones. Burmese listeners' discrimination accuracy was compared with that of Mandarin listeners and Australian English listeners. The Australian English group was included as a control group with a non-tonal background. Accuracy of perception of six tone pairs (T1-T2, T1-T3, T1-T4, T2-T3, T2-T4, T3-T4) was assessed in a discrimination test. Our main findings are 1) Mandarin listeners were more accurate than non-native listeners in discriminating all tone pairs, 2) Australian English listeners naïve to Mandarin were more accurate than similarly naïve Burmese listeners in discriminating all tone pairs except for T2-T4, and 3) Burmese listeners had the greatest trouble discriminating T2-T3 and T1-T2. Taken together, the results suggest that merely possessing lexical tones in L1 may not necessarily facilitate the perception of non-native tones, and that the active use of phonation type in encoding L1 tones may have played a role in Burmese listeners' less than optimal perception of Mandarin tones.